Solving Some Fractional Partial Differential Equations by Invariant Subspace and Double Sumudu Transform Methods - Kadhem, Hasan Shather; Hasan, Sameer Qasim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this paper, several types of space-time fractional partial differential equations has been solved by using most of special double linear integral transform â€double  Sumudu â€. Also, we are going to argue the truth of these solutions by another analytically method â€œinvariant subspace methodâ€. All results are illustrative numerically and graphically.